The Effect of Giving Dark Chocolate on Reducing Menstrual Pain in Primary Dysmenorrhoea in Employees of Cabangbungin General Hospital, Bekasi Regency in 2023 - Silfia Nuzulus Sa’idah; Maulida Lathifah; Evita Anindya Bestari (HM Publisher, 2023)
Background. Dark chocolate can be used as an alternative to overcome pain during menstruation time because it contains many benefits in the health sector. This study aimed to determine the effect of giving dark chocolate on reducing dysmenorrhea menstrual pain in female employees of the Cabangbungin General Hospital, Bekasi Regency, in 2023. Methods. This study was an experimental study of 32 research subjects. Data analysis was carried out univariate and bivariate using SPSS version 25. Results. Statistical test results used test paired sample t-test obtained ρ value = 0.000, with a value of α = 0.05 (ρ <α), indicating that there is an effect of giving dark chocolate to reducing dysmenorrhea menstrual pain. Conclusion. There was an effect of giving dark chocolate to reducing dysmenorrhea menstrual pain in female employees of the Cabangbungin General Hospital, Bekasi Regency, in 2023.